2017
DOI: 10.1111/tme.12461
|View full text |Cite
|
Sign up to set email alerts
|

Provision of cellular blood components to CMV‐seronegative patients undergoing allogeneic stem cell transplantation in the UK: survey of UK transplant centres

Abstract: The survey demonstrated a surprisingly high rate (22.7%) of centres continuing to provide blood components from CMV-seronegative donors despite SaBTO guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The same is true for the hemoglobin 70 g/L threshold in most instances. In addition, try to reduce synchronous parenteral nutrition (if possible) in patients with excellent transfusion needs [ 17 , 65 , 98 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Areas Of Particular Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is true for the hemoglobin 70 g/L threshold in most instances. In addition, try to reduce synchronous parenteral nutrition (if possible) in patients with excellent transfusion needs [ 17 , 65 , 98 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Areas Of Particular Interestmentioning
confidence: 99%
“…The administration of allogenic grafts to the recipients confers the risk of infectious and non-infectious disease transmission [ 48 , 98 , 99 , 108 ]. This risk can be minimized by thorough donor testing.…”
Section: Areas Of Particular Interestmentioning
confidence: 99%
“…1 In 2012 the Advisory Committee on the Safety of Blood, Tissues and Organs (SaBTO) released a position statement on blood components tested for CMV immunoglobulin (Ig)G; for CMV-seronegative patients undergoing HSCT CMV-unselected (CMV-U) leucocyte-reduced components can be safely transfused with no increased risk of transfusion-transmitted CMV infection. 2 According to a recent UK wide survey, nearly 70% of allogeneic stem cell transplant centres in the UK now transfuse CMV-U components to all potential transplant recipients irrespective of serostatus, 3 in line with the SaBTO guidance.…”
Section: Introductionmentioning
confidence: 99%
“…13 A survey of UK allogeneic transplant centres reported that nearly 70% of centres transfuse CMV-unselected components regardless of recipient CMV status. 14 In a survey of United States centres, 34Á6% of respondents do not view leucocyte reduction and utilisation of seronegative products as equally effective. Approximately 35% of adult HCT programmes, and 45% of paediatric HCT programmes, transfuse seronegative patients with seronegative products only.…”
mentioning
confidence: 99%
“…Differing transfusion practices, leucocyte reduction methodologies and qualifications among nations are additional confounding variables that may impact the risk of passive antibody transfer 13 . A survey of UK allogeneic transplant centres reported that nearly 70% of centres transfuse CMV‐unselected components regardless of recipient CMV status 14 . In a survey of United States centres, 34·6% of respondents do not view leucocyte reduction and utilisation of seronegative products as equally effective.…”
mentioning
confidence: 99%